A targeted correction for arctic oscillation biases in seasonal forecasts - Ji-Han Sim; Baek-Min Kim; Ha-Rim Kim; Gaeun Kim; A-Young Lim; Yoo-Rim Jung; Ju Heon Kim; Geun Young Kim; Steven Cocke (Climate Dynamics, 2026)

Identification of genetic signatures of positive selection in apes linked to life-history trait adaptations - Yoo-Rim Roh; Kiejung Park; Young Jun An; Hyung-Soon Yim; Jung-Hyun Lee (Genes & Genomics, 2025)

Molecular characterization of positively selected genes contributing aquatic adaptation in marine mammals - Yoo-Rim Roh; Hyung-Soon Yim; Kiejung Park; Jung-Hyun Lee (Genes & Genomics, 2024)

An economically advantageous amorphous solid dispersion of the fixed combination of lopinavir and ritonavir - Taek-Seon Yun; Minwoo Jung; Ki-Hyun Bang; Hong-Ki Lee; Minki Jin; Hyelim Yoo; Jong-Hee Won; Bomin Song; Yu-Rim Hwang; Jong-Suep Baek; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2023)

The Analyses of Cetacean Virus-Responsive Genes Reveal Evolutionary Marks in Mucosal Immunity-Associated Genes - Oksung Chung; Ye-Eun Jung; Kyeong Won Lee; Young Jun An; Jungeun Kim; Yoo-Rim Roh; Jong Bhak; Kiejung Park; Jessica A. Weber; Jaehun Cheong; Sun-Shin Cha; Jung-Hyun Lee; et al. (Biochemical Genetics, 2022)
Viruses are the most common and abundant organisms in the marine environment. To better understand how cetaceans have adapted to this virus-rich environment, we compared cetacean virus-responsive genes to those from terrestrial mammals. We identified virus-responsive gene sequences in seven species of cetaceans, which we compared with orthologous sequences in seven terrestrial mammals. As a result of evolution analysis using the branch model and the branch-site model, 21 genes were selected using at least one model. IFN-ε, an antiviral cytokine expressed at mucous membranes, and its receptor IFNAR1 contain cetacean-specific amino acid substitutions that might change the interaction between the two proteins and lead to regulation of the immune system against viruses. Cetacean-specific amino acid substitutions in IL-6, IL-27, and the signal transducer and activator of transcription (STAT)1 are also predicted to alter the mucosal immune response of cetaceans. Since mucosal membranes are the first line of defense against the external environment and are involved in immune tolerance, our analysis of cetacean virus-responsive genes suggests that genes with cetacean-specific mutations in mucosal immunity-related genes play an important role in the protection and/or regulation of immune responses against viruses.

COCH-related autosomal dominant nonsyndromic hearing loss: a phenotype–genotype study - Kyung Seok Oh; Daniel Walls; Sun Young Joo; Jung Ah Kim; Jee Eun Yoo; Young Ik Koh; Da Hye Kim; John Hoon Rim; Hye Ji Choi; Hye-Youn Kim; Seyoung Yu; Richard J. Smith; et al. (Human Genetics, 2022)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.

Nobiletin improves emotional and novelty recognition memory but not spatial referential memory - Jiyun Kang; Jung-Won Shin; Yoo-rim Kim; Kelley M. Swanberg; Yooseung Kim; Jae Ryong Bae; Young Ki Kim; Jinwon Lee; Soo-yeon Kim; Nak-Won Sohn; Sungho Maeng (Journal of Natural Medicines, 2017)

Purification and Anticoagulant Activity of a Fucoidan from Korean Undaria pinnatifida Sporophyll - Woo-Jung Kim; Sung-Min Kim; Hyun-Guell Kim; Hye-Rim Oh; Kyung-Bok Lee; Yoo-Kyung Lee; Yong-Il Park (Algae, 2007)